Ferroelectric and Piezoelectric Properties of BiFeO3‐Based Piezoelectric Ceramics. Issue 12 (14th January 2020) - Habib, Muhammad; Lee, Myang Hwan; Kim, Da Jeong; Choi, Hai In; Kim, Myong-Ho; Kim, Won-Jeong; Song, Tae Kwon
Abstract : Bismuth ferrite‐based bulk ceramics (1– x )Bi0.97 Sm0.08 FeO3 – x BaTiO3 (BSF– x BT with x  = 0.00 FC, x  = 0.00 WQ, x  = 0.01 WQ, x  = 0.03 WQ, and x  = 0.05 WQ, where FC is the furnace cooled and WQ is the water quenched) are synthesized by a conventional solid‐state reaction method followed by WQ process. The WQ procedure (compared with FC) dramatically improves the remnant polarization ( P r ) of x  = 0.00 ceramic from 11 to 21 μC cm −2 . BT incorporation gradually reduces the coercive field ( E c ) and P r significantly enhances to 28.5 μC cm −2 (at x  = 0.03) with fully saturated P – E hysteresis loops. The temperature‐dependent ferroelectric properties reveal that the corresponding P r values improve with the rising temperature; this behavior may be related to the thermally activated domain walls motion. Symmetric and closed electromechanical strain–electric field ( S–E ) curves are obtained with a maximum strain of S max  = 0.05% for an optimum composition together with high charge sensor constant ( d 33  = 56 pC N −1 ). The structural and electrical properties of the investigated ceramics are presented in detail. Abstract : (1− x )Bi0.97 Sm0.08 FeO3 − x BaTiO3 ceramics (with x  = 0.00–0.05) are synthesized through the conventional solid‐state reaction method. The remanent polarizaion of the furance cooled ceramic significantly enhances from 12 to 28.5 μC cm −2 with water quenching and BaTiO3 addition. High piezoelectric performace ( d 33  = 56 pC N −1 and d 33 *  = 40 pm V −1 ) obatins for an optimum composition (with x  = 0.03).